A Aktivitas Antioksidan dan Penetapan Kadar Flavonoid Daun Sirih Merah (Piper crocatum Ruiz & Pav) Dengan Variasi Ukuran Partikel Serbuk Simplisia - Oktavia, Rissa; Rohama, Rohama; Saputri, Rina (LPPM Universitas Sari Mulia, 2023)
Background: Red betel (Piper crocatum Ruiz & Pav) is a medicinal plant that is used empirically by the people of Tehang, Central Kalimantan for wound healing. The ability of red betel leaves to heal wounds is associated with the anti-inflammatory properties of the secondary metabolites of the flavonoid class contained therein which also have a role as a source of antioxidants. Particle size will affect the amount of bioactive compounds in an extract. Objective: To determine the difference in antioxidant activity and flavonoid content ethanol extract of red betel leaf in a variation of particle size simplisia powder. Methods: True experimental quantitative research which divided into two experimental groups, namely red betel leaf extract with a mesh particle size of 40/60 and 60/80. Testing of antioxidant activity with the DPPH method and determining the levels of flavonoids with the UV-Vis Spectrophotometry method. Results: The results of antioxidant activity based on IC50 values at 40/60 and 60/80 mesh particle sizes is 5.96 ppm and 2.74 ppm. The results of flavonoid content determination at 40/60 and 60/80 mesh particle size is 1.448 mg QAE/g and 3.5 mg QAE/g. Statistical analysis with the Mann Whitney test showed a significant difference (p value 0.025 <0.05). Conclusion: There is a significant difference with the variation of particle size on the antioxidant activity and levels of flavonoids. The highest antioxidant activity and flavonoid levels were observed in extracts with a mesh particle size of 60/80. The smaller the particle size, the stronger the antioxidants and the higher the levels of flavonoids.